EFFORT TO SURVIVE IN YANN MARTEL’S NOVEL LIFE OF PI - Ayu Annisya Rachman Nasution; Zulfan Sahri; Asnani Asnani (JOURNAL OF LANGUAGE, 2023)
This study deals with the analysis of the protagonist’s effort to survive in Yann Martel’s novel Life of Pi. This study focuses on three topics. The topics are reading sea survival guidebook, getting defence from the tiger and defending his life.  The novel talks about an Indian teenager, who is trapped in the middle of the fierce sea for 227 days with a Bengal tiger named Richard Parker. To survive, he makes several attempts. He reads survival guidebook found in the lifeboat. He gets defense from the tiger. Then, he defends a life. In this study, the theory of sea survival was applied. This study used descriptive qualitative method because the process of the result and discussion are accomplished descriptively. By applying descriptive qualitative method, this research can prove that protagonist has some efforts to survive because the topics of the protagonist's efforts to survive really exist and can be faced by the protagonist. Based on the research analysis, three efforts to survive are found in the novel. First, The protagonist,  Pi does several things to read sea survival guidebook, to get defence from the tiger, and to defend his life.